2012
DOI: 10.1002/eji.201242768
|View full text |Cite
|
Sign up to set email alerts
|

HCV‐infected hepatocytes drive CD4+CD25+Foxp3+ regulatory T‐cell development through the Tim‐3/Gal‐9 pathway

Abstract: Hepatitis C virus (HCV) is remarkable at disrupting human immunity to establish chronic infection. Accumulation of regulatory T cells (Tregs) and up-regulation of inhibitory signaling pathways (such as Tim-3/Gal-9) play pivotal roles in suppressing antiviral effector T cells (Teffs) that are essential for viral clearance. While Tim-3/Gal-9 interactions have been shown to negatively regulate Teffs, their role in regulating Tregs is poorly understood. To explore how Tim-3/Gal-9 interactions regulate HCV-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 30 publications
3
64
0
2
Order By: Relevance
“…We have recently demonstrated that HCV not only upregulates Tim-3 expression on activated T cells, but also a Tim-3 ligand, galectin-9 (Gal-9), on the surfaces of infected hepatocytes (37). The HCV-mediated Tim-3/Gal-9 interactions drive naive CD4 ϩ T cells differentiation into CD4…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently demonstrated that HCV not only upregulates Tim-3 expression on activated T cells, but also a Tim-3 ligand, galectin-9 (Gal-9), on the surfaces of infected hepatocytes (37). The HCV-mediated Tim-3/Gal-9 interactions drive naive CD4 ϩ T cells differentiation into CD4…”
Section: Discussionmentioning
confidence: 99%
“…ϩ CD25 ϩ Foxp3 ϩ T regulatory cells (Tregs) but inhibit CD4 ϩ CD25 ϩ Foxp3 Ϫ T effector cells (Teffs), indicating an immunomodulatory role of HCV-infected hepatocytes (37,38). We show here that HCV also promotes TLR-mediated STAT3 signaling within the virally infected microenvironment and induces a heterodimeric cytokine, IL-23, while inhibiting its counterpart cytokine, IL-12, thereby shifting the balance of antiviral immunity toward a condition favoring viral persistence and autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tim-3 + Tregs tend to resist apoptotic signals and show a higher capacity to proliferate, leading to Treg accumulation. Moreover, Ji et al [40] have reported that HCV infection leads to elevated Gal-9 and TGF-β production in hepatocytes.…”
Section: Tim-3 and Effector T Cellsmentioning
confidence: 99%
“…Co-culture of HCV-infected hepatocytes and CD4 + T cells induces increased Tim-3 expression on CD4 + T cells, and the Tim-3/Gal-9 interaction enhances TGF-β/ IL-10 production by CD4 + T cells, which accelerates the differentiation of CD4 + T cells into Tregs [40] . However, the regulatory effects of Tim-3 on Tregs in HBV infection remain to be clarified.…”
Section: Tim-3 and Treg/th17 Cellsmentioning
confidence: 99%